Experimental Investigations on Microwave-Current Assisted Sintering Process and Oxidation of Graphite Die at High Temperature - Al-Jothery, H.K.M. (Universiti Malaysia Pahang, 2021)
In the current-assisted sintering technique, graphite is mainly used to fabricate die and other components (such as electrodes and spacers) because of its excellent thermoelectric properties, high melting point and high ratio of the tensile strength to the compressive strength. As widely known, graphite is one of the brittle materials, and the failure is difficult to be anticipated before it happens. Besides, there is a lack of information about the effects of sintering process, environment and impurity on the graphite structure of the furnace, especially the die, which is the weakest part of the graphite structure. Therefore, the effects of electrical field and oxidation on the graphite die of microwave-current assisted sintering apparatus were investigated at a high temperature of 600â1900Â°C based on physical characteristics and mechanical strength. In this article, the spark discharge phenomenon was experimentally proved during the sintering process of nonconductive material. The tensile strength of the upper punch after the sintering process was 20.2 higher than the pristine one because of the transforming of micro-graphite to carbon nanotubes which increased with increasing the temperature. On the other hand, the tensile strengths of graphite lower punch and sleeve were slightly dropped. While, the oxidation of GW-6S graphite in the air caused a mass loss that led to the reduction in tensile and compressive strengths. Â© The Authors 2021. Published by Penerbit UMP. This is an open access article under the CC BY license.